THE USE OF FILM MEDIA TO IMPROVE STUDENT ACHIEVEMENT IN SOCIAL STUDIES SUBJECTS - Rubiani, Uzma Salma (Journal Learning Geography, 2024)
The purpose of this study was to describe: (1) Planning Learning, (2) Learning Activities, (3) Learning Achievement study, (4) Evaluation of Learning with media. The method used is classroom action research carried out with 3 cycles. Data collection tools included observation sheet, photo documentation, interviews and tests. The results of this study indicate: (1) Increase Value of Learning Planning, the results of cycle 1 is 3.61 (72%), cycle 2 is 3.73 (74%), cycle 3 is 3.81 (76%), (2) Improved student learning activities, cycle 1 students who are active 51%, of the six indicators of activity, three indicator of activity is reached (note, listening and discussion), while three indicators of the activity has not been achieved (listening to the teacher, asking and answering questions), cycle 2 students 71% active, the activity of the six indicators, four indicators of activity is reached (listening to the teacher, notes, listen and talk) while the two indicators has not been achieved (asking and answering questions), cycle 3 students who are active and 94% of the 6 indicators have been achieved in overall (listening to the teacher, taking notes, listening, discussing, asking and answering questions), (3) Improved student learning outcomes, students who complete a cycle of 55.1%, students who complete the cycle 2 and cycle 3 86% of students who complete 93 %, (4) Improvement of evaluation of learning, 1 cycle at 80%, 90% cycle 2 and cycle 3 reached 98%.